Pharmaceutical Care in Primary Care in Brazil compared to Spain and the United Kingdom – Literary review (Research, Society and Development, 2022)
Introduction: Pharmaceutical assistance allows the primary care pharmacist to guide patients, through clinical consultation, on the proper use of prescribed drugs, making treatment safer and more effective, curbing polypharmacy problems and automatically collaborating in the reduction of health system costs. Materials and methods: A literature review was carried out comparing Spain and the United Kingdom with Brazil, taking into account that these countries were developed and had good references regarding Pharmaceutical Care in Primary Care. Results and discussion: In the technical-assistance sphere, Brazilian pharmacists can dispense over-the-counter medications (MIPs), carry out consultations and monitor patients. In the United Kingdom, in addition to prescribing some drugs, during the clinical consultation, pharmacists can act in prevention, detection and discussions in order to solve the risks of drug-related problems. In Spain, the pharmacist has a guiding role and cannot prescribe medication, during consultations, pharmacological indications are made in order to solve problems related to medication, effectively contributing to the control of pharmacotherapeutic treatment together with doctors and nurses. In Brazil and the United Kingdom, restrictions were reported that made it difficult to apply pharmaceutical care in practice, such as the accumulation of managerial activities, inadequate facilities, lack of managerial support and inappropriate resources, in addition to the lack of recognition from the community and other professionals in the field. health. In the Spanish public network, pharmaceutical assistance is already well established, however, in private community pharmacies, professionals report problems similar to those mentioned above. Conclusion: It was evident the need to increase the awareness of users and other agents in the area about the importance of pharmaceutical care in primary care.